Between Body, Dance and Costume (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2022)
This article proposes to investigate some of the relationships between body, movement, dance and costumes, from the perspective of the body as a wrapper of the soul, presenting some reflections that surround it in philosophy and in the dance movement. The participation of the costumes in the dance and its relationship with visuality, ergonomics, materials, volumes, and space will be highlighted, jointly emphasizing the light reflected in the scene. Also related to the researched elements some representations of bodies in classical, modern, and contemporary dances, characterized by their proper costumes.
Keywords: body; Philosophy; dance; costume